People’s Perceptions and Experiences Regarding Nepal Health Insurance Program: Evidence of Bharatpur - Pradhan, Bijay Lal; Bista, Shradhda (Morgan Journal of Interdisciplinary Research Studies, 2024)
The Nepal Health Insurance Program (NHIP) was established in 2016 to achieve universal health coverage in Bharatpur and address public healthcare issues. Despite its unique features, such as contracts with healthcare providers and additional support for open populations, dissatisfaction among users has arisen due to unfulfilled promises. This study investigates Bharatpur residents’ NHIP awareness, participation trends, enrollment factors, and overall satisfaction. The research, utilizing a survey with 39 participants, emphasizes user-friendliness and positive correlations between perceived program convenience and healthcare quality belief. Main findings stress the need for improved communication and information accessibility. Concerns include medication availability, fraudulent billing, and care standards. Recommendations include increased awareness, prompt claims resolution, expanding healthcare facilities, and addressing fraud. The study contributes to healthcare improvement discussions by advocating customized approaches, addressing service quality issues, and involving the community in decision-making. In summary, NHIP, launched for universal health coverage in Bharatpur, faces challenges of user dissatisfaction and unmet promises, emphasizing the importance of communication and addressing key issues.